2016
DOI: 10.1016/j.carbpol.2016.08.016
|View full text |Cite
|
Sign up to set email alerts
|

Surface stiffening and enhanced photoluminescence of ion implanted cellulose – polyvinyl alcohol – silica composite

Abstract: Novel Cellulose (Cel) reinforced polyvinyl alcohol (PVA)-Silica (Si) composite which has good stability and in vitro degradation was prepared by lyophilization technique and implanted using N 3+ ions of energy 24 keV in the fluences of 1 × 10 15 , 5 × 10 15 and 1 × 10 16 ions/cm 2 . SEM analysis revealed the formation of microstructures, and improved the surface roughness on ion implantation. In addition to these structural changes, the implantation significantly modified the luminescent, thermal and mechanica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 58 publications
(57 reference statements)
1
7
0
Order By: Relevance
“…Liu et al [ 56 ] reported that the unique emission behaviors of cellulose may originate from the electron-rich oxygen and/or glucose units, which also confirms the aggregation-induced or crystallization-induced emissions from cellulose. Shanthini et al [ 57 ] also revealed that cellulose consisted of two intense PL bands at about 420–440 nm and 480–490 nm. On the other hand, the decreasing PL intensity in cellulose/Ag/TiO 2 was attributed to a decrease in the recombination rate of charge carriers in TiO 2 and the improvement of charge separation.…”
Section: Resultsmentioning
confidence: 99%
“…Liu et al [ 56 ] reported that the unique emission behaviors of cellulose may originate from the electron-rich oxygen and/or glucose units, which also confirms the aggregation-induced or crystallization-induced emissions from cellulose. Shanthini et al [ 57 ] also revealed that cellulose consisted of two intense PL bands at about 420–440 nm and 480–490 nm. On the other hand, the decreasing PL intensity in cellulose/Ag/TiO 2 was attributed to a decrease in the recombination rate of charge carriers in TiO 2 and the improvement of charge separation.…”
Section: Resultsmentioning
confidence: 99%
“…PVA has previously been used to carry and sustain the release of biologically active molecules. 25,26 Platelet-rich fibrin (PRF) is a second-generation platelet concentrate with a simplified preparation method that does not require the addition of thrombin or calcium chloride. 27,28 PRF has been reported to have the potential to facilitate hemostasis, wound healing, and the differentiation of preosteoblasts due to the presence of secreted growth factors.…”
Section: Introductionmentioning
confidence: 99%
“…For inert polymers, an ion beam may produce ultra-thin conducting or reflecting films below the polymer surface. Among others, this technique has been applied for strain gauge applications [ 98 ] or for PVA, for increasing the degree of crystallinity and microhardness [ 57 ], for fabricating planar light guides [ 99 ], and for enhanced photoluminescence [ 58 ].…”
Section: Tuning the Optical And Electronic Properties Of Doped Pva Filmsmentioning
confidence: 99%
“…Analyzed with m-line spectroscopy, a 3–5 μm thickness film (guiding light up to three modes) irradiated with a low implantation dose (<10 14 ions/cm 2 ) leads to a total waveguide loss values lower than 2 dB/cm (for 633 nm wavelength ). A cellulose reinforced polyvinyl alcohol silica (Cel-PVA-Si) composite implanted using N 3+ ions [ 58 ], shows significantly modified luminescent, thermal and mechanical properties, also as an electric conductivity improvement by about 25%. FTIR analysis reveals that the ion implanted samples undergo bond breakage.…”
Section: Tuning the Optical And Electronic Properties Of Doped Pva Filmsmentioning
confidence: 99%